2011
DOI: 10.1159/000332398
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dequalinium Chloride Vaginal Tablets (Fluomizin®) and Clindamycin Vaginal Cream in the Treatment of Bacterial Vaginosis: A Single-Blind, Randomized Clinical Trial of Efficacy and Safety

Abstract: Aims: To investigate if vaginal application of dequalinium chloride (DQC, Fluomizin®) is as effective as vaginal clindamycin (CLM) in the treatment of bacterial vaginosis (BV). Methods: This was a multinational, multicenter, single-blind, randomized trial in 15 centers, including 321 women. They were randomized to either vaginal DQC tablets or vaginal CLM cream. Follow-up visits were 1 week and 1 month after treatment. Clinical cure based on Amsel’s criteria was the primary outcome. Secondary outcomes were rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 48 publications
1
73
0
6
Order By: Relevance
“…Briefly, the Prestwick library of FDA-approved compounds (∼2,000) at a concentration of ∼10 μM was screened against the yeast strain WT[Su9-URA3]. The strain was aliquotted into 384-well pates consisting of 24 columns followed by compound addition with robotic pinning into the assay wells (column [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in minimal glucose media lacking uracil. For a negative control of cell growth, column 2 contained the WT[Su9-URA3] strain with 1% DMSO.…”
Section: An In Vivo Screen For Inhibitors Of Mitochondrial Protein Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the Prestwick library of FDA-approved compounds (∼2,000) at a concentration of ∼10 μM was screened against the yeast strain WT[Su9-URA3]. The strain was aliquotted into 384-well pates consisting of 24 columns followed by compound addition with robotic pinning into the assay wells (column [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in minimal glucose media lacking uracil. For a negative control of cell growth, column 2 contained the WT[Su9-URA3] strain with 1% DMSO.…”
Section: An In Vivo Screen For Inhibitors Of Mitochondrial Protein Trmentioning
confidence: 99%
“…1A). DECA has been approved as an antibacterial treatment for oral and vaginal applications (18). Moreover, DECA is used as a "nano-particle" to deliver cargo to the mitochondria (19,20).…”
Section: An In Vivo Screen For Inhibitors Of Mitochondrial Protein Trmentioning
confidence: 99%
“…In in vitro fertilization procedures, a relation was found between BV and implantation failures (Ralph et al, 1999), but this relation was not confirmed in another observation (Liversedge et al, 1999). Furthermore, amongst these patients a clear relation of BV with tubal infertility was present, (Liversedge et al, 1999;Wilson et al, 2002) indicating indirectly BV is a risk factor for ascending infection and tubal damage. Interestingly, in one study, not BV, but decreased lactobacilli (AVF) was found to be the risk factor of implantation failure at IVF (Eckert et al, 2003).…”
Section: Miscarriagementioning
confidence: 87%
“…Some of these compounds, such as dequalinium chloride, nifuratel and chlorhexidine have been tested in clinical trials for effectiveness compared to traditional therapies, showing positive results [114,135,187] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%